Lethal means safety for Asian American, Native Hawaiian, and Pacific Islander Veterans: Insights from key informants - Lindsey L. Monteith; Evan R. Polzer; Ryan Holliday; Darrin M. Aase; Joseph A. Simonetti (PLoS ONE, 2026)
Aims Asian American, Native Hawaiian, and Pacific Islander (AANHPI) Veterans are more likely to use suffocation and less likely use firearms in suicide deaths, relative to Veterans overall. Information to inform tailoring of lethal means safety (LMS) interventions for AANHPI Veterans is limited. We elicited subject matter experts’ perspectives regarding LMS among AANHPI Veterans, including awareness of differences in suicide methods and insights regarding LMS considerations. Method Qualitative interviews were conducted with forty-three key informants in the Continental U.S. (CONUS), Hawaii, and Guam in 2022–2024. Interview transcripts were examined via deductive content analysis for this secondary analysis. Results Key informants noted an increased use of hanging among AANHPI Veterans and in specific regions (e.g., Pacific Islands), though mention of hanging/suffocation was specific to key informants in Hawaii and Guam. Key informants noted that LMS efforts do not address hanging, emphasizing the need for resources that address hanging and that are tailored to local contexts. Some key informants also noted the lower use of firearms as a suicide method among AANHPI Veterans, sharing potential explanations for this, while expressing concerns that recent increases in firearm access in this population could lead to increases in firearm suicide deaths. Accordingly, key informants expressed a need to understand how cultural considerations could be incorporated into firearm LMS efforts for AANHPI Veterans. Discussion Some subject matter experts, particularly those in the U.S. Pacific Islands, have awareness of the differences in suicide methods among AANHPI Veterans; however, increasing CONUS practitioners’ awareness of the increased use of hanging/suffocation as a suicide method among AANHPI Veterans may be warranted. Developing strategies to prevent suicide by hanging is crucial to preventing suicide among AANHPI Veterans. Considering potentially increased rates of firearm access among AANHPI Veterans, development of culturally responsive firearm suicide prevention efforts for this population is also warranted.